Forty Years after the War of June 1967: “Peace comes with pain and strength.” Yitzhak Rabin (American Journal of Islam and Society, 2007)
On 5 June 2007, the fortieth anniversary of the Six Day War and the Israelioccupation of Palestine, the Kay Spiritual Life Center hosted “Forty Yearsafter the War of June 1967: Is Israeli-Palestinian Peace Possible?” on thecampus of American University in Washington, DC. This panel featuredYuval Rabin (son of former Prime Minister Yitzhak Rabin; governing board,the Rabin Center), Amjad Atallah (president, Strategic Assessments Initiative),Aaron David Miller (public policy scholar, the Woodrow WilsonCenter), and Ziad Asali (president, American Task Force on Palestine; panelchair).Rabin opened by describing the Six Day War as “a war of our existence.”He discussed the importance of the Camp David, Oslo, and other negotiationsand then talked about Israel’s 1967 victory. After stating that both sidesin this continued conflict have faced hardship, he also mentioned the lack ofknowledge involving certain issues.Atallah explained how Americans are bogged down with this conflict’stechnicalities, such as the number of checkpoints, which causes them to neglectthe bigger picture. He pointed out that on 29 November 1947, the UnitedNations General Assembly passed a resolution (33 to 13) recommending thatPalestine be partitioned into two states, with over half of the land going to theJews and the rest going to the Palestinians. By May 1948, according to theUnited Nations and the State Department, 350,000 Palestinians had beenexpelled from their homes. The Arab states declared war on Israel and, outnumberedand under-equipped, 400,000 more Palestinians were expelled. Atthe time, the Israelis accepted partition and the Arabs rejected the plan. Heexplained that the Israelis rushed to the Sinai Peninsula and the Jordan riverand fully understood the rules of diplomacy. This resulted in Jordan takingover what is now the West Bank. In the course of the Six Day War, another600,000 Palestinians were displaced, some for the second time ...